Space Environment Monitoring Unit on Wentian Laboratory Cabin Module of China Space Station - Huanxin Zhang; Guohong Shen; Donghui Hou; Shenyi Zhang; Chunqin Wang; Ying Sun; Liping Wang; Jiajie Liao (Aerospace)
This article introduces the design and development of a space environment monitoring unit embedded in the versatile experimental assembly for electronic components outside the China space station’s Wentian laboratory cabin module. A newly designed comprehensive detection system is being used for the first time in this kind of detector. The sensor head of the instrument includes a silicon telescope (composed of two silicon semiconductors) for measuring the LET spectrum and radiation dose rate, a typical chip for monitoring a single-event upset, and a CR-39 plastic nuclear track detector for detecting heavy ion tracks. The two silicon sensors stacked up and down are used for measuring the LET spectrum, which ranges from 0.001 to 100 MeV·cm2/mg. A sensor charge allocation method is adopted to divide the detection range into four cascaded levels, each achieving different detection ranges separately and then concatenated together, while traditional detection methods need multiple sets of probes to achieve the same dynamic range. At the same time, using the two sensors mentioned above, the silicon absorption dose rate under two different shielding thicknesses can be obtained through calculation, ranging from 10−5 to 10−1 rad (Si)/h. Multiple calibration methods are applied on the ground. The preliminary in-orbit detection results are provided and compared with the simulation results obtained using the existing space environment model, and we analyze and discuss their differences.